Protocol for a randomised trial evaluating a preconception-early childhood telephone-based intervention with tailored e-health resources for women and their partners to optimise growth and development among children in Canada: a Healthy Life Trajectory Initiative (HeLTI Canada). Issue 2 (10th February 2021) - Dennis, Cindy-Lee; Marini, Flavia; Dick, Jennifer Abbass; Atkinson, Stephanie; Barrett, Jon; Bell, Rhonda; Berard, Anick; Berger, Howard; Brown, Hillary K; Constantin, Evelyn; Da Costa, Deborah; Feller, Andrea; et al.
Abstract : Introduction: The 'Developmental Origins of Health and Disease' hypothesis suggests that a healthy trajectory of growth and development in pregnancy and early childhood is necessary for optimal health, development and lifetime well-being. The purpose of this paper is to present the protocol for a randomised controlled trial evaluating a preconception-early childhood telephone-based intervention with tailored e-health resources for women and their partners to optimise growth and development among children in Canada: a Healthy Life Trajectory Initiative (HeLTI Canada). The primary objective of HeLTI Canada is to determine whether a 4-phase 'preconception to early childhood' lifecourse intervention can reduce the rate of child overweight and obesity. Secondary objectives include improved child: (1) growth trajectories; (2) cardiometabolic risk factors; (3) health behaviours, including nutrition, physical activity, sedentary behaviour and sleep; and (4) development and school readiness at age 5 years. Method and analysis: A randomised controlled multicentre trial will be conducted in two of Canada's highly populous provinces—Alberta and Ontario—with 786 nulliparous (15%) and 4444 primiparous (85%) women, their partners and, when possible, the first 'sibling child.' The intervention is telephone-based collaborative care delivered by experienced public health nurses trained in healthy conversation skills that includes detailed risk assessments, individualised structured management plans, scheduled follow-up calls, and access to a web-based app with individualised, evidence-based resources. An 'index child' conceived after randomisation will be followed until age 5 years and assessed for the primary and secondary outcomes. Pregnancy, infancy (age 2 years) and parental outcomes across time will also be assessed. Ethics and dissemination: The study has received approval from Clinical Trials Ontario (CTO 1776). The findings will be published in peer-reviewed journals and disseminated to policymakers at local, national and international agencies. Findings will also be shared with study participants and their communities. Trial registration number: ISRCTN13308752 ; Pre-results.